A Study on Pharmacokinetics of Acetylsalicylic Acid Mini-Tablets in Healthy Adult Males-Comparison with the Powder Formulation - Noriko Hida; Taigi Yamazaki; Yoshiaki Fujita; Hidehiro Noda; Takehiko Sambe; Kakei Ryu; Takuya Mizukami; Sachiko Takenoshita; Naoki Uchida; Akihiro Nakamura; Tsutomu Harada (MDPI AG, 2023)
Children with Kawasaki disease are prescribed acetylsalicylic acid powder as an antipyretic analgesic and antiplatelet agent; however, some of it remains in the mouth, leading to a bitter or sour taste. To address this issue, an in-hospital mini-tablet formulation of acetylsalicylic acid was developed. In order to use the mini-tablets safely and effectively, dissolution tests alone are not sufficient. Therefore, an open-label crossover study on six healthy participants was conducted to evaluate comparative pharmacokinetic parameters. The pharmacokinetic parameters of salicylic acid were Cmax: 4.80 ± 0.79 mg/L (powder; P), 5.03 ± 0.97 mg/L (mini-tablet; MT), AUC0-12: 18.0 ± 3.03 mg-h/L (P), 18.9 ± 4.59 mg-h/L (MT), those of acetylsalicylic acid Cmax: 0.50 ± 0.20 mg/L (P), 0.41 ± 0.24 mg/L (MT), AUC0-12: 0.71 ± 0.27 mg-h/L (P), 0.61 ± 0.36 mg-h/L (MT), with no significant differences between the mini-tablet and powder formulations. Although pharmacokinetic results obtained from adults cannot be directly applied to children, the results of this study are important for predicting pharmacokinetics. Furthermore, a formulation that can improve medication adherence in children who have difficulty taking acetylsalicylic acid powder, thus contributing to pediatric drug therapy.